EFFECT OF JOB SATISFACTION ON EMPLOYEES PERFORMANCE MODERATED BY JOB MOTIVATION (Case Study at Pt. Jasa Raharja (Persero) Branch Of Makassar) - Siti Aisyah (Politeknik Negeri Bengkalis, 2022)
The research is focused on (1) the effect of job satisfaction on job performance, 2) the effect of job motivation on employee performance, and 3) job motivation as a moderator in explaining the effect of job satisfaction on employee performance. The approach used in this research was a quantitative approach with tangible data on numbers and proving the hypothesis . The data source is from respondents through questionnaires distributed. The population was all permanent employees at PT. Jasa Raharja (Persero) Branch of Makassar consisting of 30 people Â The results showed Job satisfaction provides simultaneous effect on employee performance improvement. It is because the indicator of employee performance (X1) denotes big effect on the indicator of payroll. This is due to the evidence that on the indicator of work motivation (X2) there is a big effect on the indicators of self-esteem. The variable of job motivation can be moderating the effect Â of job satisfaction on employee performance